Transformation, Dynamics, and Intellectual Conflicts in Indonesian Islamic Higher Education : Tradition Vs Modernity - Susanto, Nanang Hasan; Kholis, Nur (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to investigate the presence of a transformation process, dynamics, and conflicting thoughts inside three Islamic Higher Education institutions in Indonesia. Subsequently, an analysis is conducted to examine the ramifications of this transformation and dynamics on the state life of Indonesian citizens. This study uses a qualitative descriptive method. The data were acquired through interviews conducted with actors from three PTKIs (K.H. Abdurrahman Wahid Pekalongan, UIN Raden Mas Said Surakarta, and UIN Walisongo Semarang), as well as through observation and documentation studies. The collected data were further analysed through an inductive process using indicators that assess rational and traditional religious perspectives. The findings reveal that the three Islamic Higher Education institutions underwent a transformation from conventional religious beliefs to rational ones. Within this transformation process, dynamics and conflicts of thought inevitably emerged. The findings show that such dynamics not only influence the development of religious education within PTKIs but also shape the broader life of the Indonesian state. In this regard, PTKIs play a strategic role in shaping education policy and social life, particularly by promoting inclusive curricula, fostering tolerance, and strengthening community empowerment in Indonesia.